Calibrer un modèle d’évolution de l’occupation du sol urbain. L’exemple de Belfort - Jean-Philippe Antoni (Cybergeo)
Today's French legislation and the current town-planning principles put a special emphasis on the notion of territorial project and prospect. It can be based on several simulations and also require modelling. The type of simulation described here includes three complementary stages to successively quantify, localize and differentiate the urban area’s probable future changes. This kind of modelling must also rest on a sturdily thought-out estimate of the relevant parameters. In the case we are talking about, the study of previous situations provides several indicators to define the coefficients that are to be inserted into the models. The example of the town of Belfort is used to illustrate the method of urban modelling and model calibrating as a whole.